IMPLEMENTASI MODEL PERAMBATAN RETAK CORPUS UNTUK ANALISA TENGGANG CACAT STRUKTUR PESAWAT TERBANG - Tafsir Dwimunali, Muhammad
Abstract: Crack growth prediction is an important part in aircraft structural analysis. Currently, there are some models of crack growth prediction, but linear model - i.e. prediction model that does not take into account the interaction effects - is used in many aircraft industries, including IPTN. Linear model is used because it gives conservative predictions. During the last two decades, non-linear models are developed to replace the linear model, because it is expected that using the non-linear model gives a closer life prediction to the test results. One of the non-linear models is CORPUS model, which is the main topic in this research. As part of this research, a software is written to predict crack growth life with CORPUS model. In this software, a number of beta factors (geometry correction factors) are included, and it is possible to add other geometry correction factors. Calculation of geometry correction factors with compounding method is possible as well. The result of this research shows that CORPUS model gave a better prediction than linear model, closer to the test result, and the life predictions are still below the test results.